Comparison of different segments in the fixation of thoracolumbar fractures: a Bayesian network meta-analysis. Issue 7 (July 2022) - Ma, Ming-ling; Dong, Hui; Yu, Hang; Ruan, Bin-jia; Xu, Xiao-hang; Tao, Yu-ping; Wang, Yong-xiang; Gu, Jia-xiang
Abstract: Background: Posterior internal fixation (PIF) is commonly used in the treatment of thoracolumbar fracture (TLF), but there is still no standard for the number of fixed segments. The objective of this meta-analysis was to evaluate the efficacy and safety of short segment (SS), intermediate segment (IS) and long segment (LS) in the fixation of TLF. Methods: Two authors independently searched through PubMed, Embase, Cochrane Library and Web of Science for studies of thoracolumbar fracture treated by posterior internal fixation, which were published until the end of April 2021. The Aggregate Data Drug Information System (ADDIS) software was used for data evaluation according to the Markov chain Monte Carlo (MCMC) method based on the Bayesian theorem. Results: Nineteen trials evaluating a total of 970 patients were enrolled in these studies, of which 340 in the SS group, 429 in the IS group and 201 in the LS group. For anterior vertebral height ratio (AVHR), IS had the highest AVHR, LS had the second highest AVHR. IS also ranked first in reducing visual analogue scale (VAS), SS ranked second. For sagittal Cobb's angle (SCA), LS had the lowest SCA and IS had the second lowest SCA. In terms of adverse events, IS had the lowest implant failure rate and LS had the second lowest implant failure rate. Conclusions: IS may be the most desirable treatment option for TLF in reducing SCA, implant failure rate, VAS, and improving AVHR. However, more randomized controlled trials are needed to verify these results.